Hyperbolic Metamaterials via Hierarchical Block Copolymer Nanostructures. Issue 7 (8th February 2021) - Murataj, Irdi; Channab, Marwan; Cara, Eleonora; Pirri, Candido F.; Boarino, Luca; Angelini, Angelo; Ferrarese Lupi, Federico
Abstract: Hyperbolic metamaterials (HMMs) offer unconventional properties in the field of optics, enabling opportunities for confinement and propagation of light at the nanoscale. In‐plane orientation of the optical axis, in the direction coinciding with the anisotropy of the HMMs, is desirable for a variety of novel applications in nanophotonics and imaging. Here, a method for creating localized HMMs with in‐plane optical axis, based on block copolymer (BCP) blend instability, is introduced. The dewetting of BCP thin film over topographically defined substrates generates droplets composed of highly ordered lamellar nanostructures in hierarchical configuration. The hierarchical nanostructures represent a valuable platform for the subsequent pattern transfer into a Au/air HMM, exhibiting hyperbolic behavior in a broad wavelength range in the visible spectrum. A computed Purcell factor as high as 32 at 580 nm supports the strong reduction in the fluorescence lifetime of defects in nanodiamonds placed on top of the HMM. Abstract : In this work, the fabrication of hyperbolic metamaterial (HMM) with in‐plane optical axis, based on self‐assembled block copolymers (BCPs), is reported. Hybrid Au/air metamaterial obtained by transfer pattern of dewetted BCPs exhibits a hyperbolic behavior responsible for a strong reduction of the fluorescence lifetime of nitrogen‐vacancy centers. These results are supported by the high Purcell factor computed by effective medium approximation and finite element method.